A cluster of mesopontine GABAergic neurons suppresses REM sleep and curbs cataplexy - Ze-Ka Chen; Hui Dong; Cheng-Wei Liu; Wen-Ying Liu; Ya-Nan Zhao; Wei Xu; Xiao Sun; Yan-Yu Xiong; Yuan-Yuan Liu; Xiang-Shan Yuan; Bing Wang; Michael Lazarus; et al. (Cell Discovery, 2022)
Abstract Physiological rapid eye movement (REM) sleep termination is vital for initiating non-REM (NREM) sleep or arousal, whereas the suppression of excessive REM sleep is promising in treating narcolepsy. However, the neuronal mechanisms controlling REM sleep termination and keeping sleep continuation remain largely unknown. Here, we reveal a key brainstem region of GABAergic neurons in the control of both physiological REM sleep and cataplexy. Using fiber photometry and optic tetrode recording, we characterized the dorsal part of the deep mesencephalic nucleus (dDpMe) GABAergic neurons as REM relatively inactive and two different firing patterns under spontaneous sleep–wake cycles. Next, we investigated the roles of dDpMe GABAergic neuronal circuits in brain state regulation using optogenetics, RNA interference technology, and celltype-specific lesion. Physiologically, dDpMe GABAergic neurons causally suppressed REM sleep and promoted NREM sleep through the sublaterodorsal nucleus and lateral hypothalamus. In-depth studies of neural circuits revealed that sublaterodorsal nucleus glutamatergic neurons were essential for REM sleep termination by dDpMe GABAergic neurons. In addition, dDpMe GABAergic neurons efficiently suppressed cataplexy in a rodent model. Our results demonstrated that dDpMe GABAergic neurons controlled REM sleep termination along with REM/NREM transitions and represented a novel potential target to treat narcolepsy.